2014
DOI: 10.3189/2014jog13j079
|View full text |Cite
|
Sign up to set email alerts
|

Snow particle characteristics in the saltation layer

Abstract: Shadowgraphy was employed to study snow saltation in boundary-layer wind tunnel experiments with fresh, naturally deposited snow. The shadowgraphy method allowed for a temporally and spatially high-resolution investigation of snow particle characteristics within a measurement area of up to 50 mm × 50 mm. Snow particle size and number characteristics, and their variation with height in the saltation layer, were analysed. The following observations and findings were made for the saltation layer: (1) the particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
4
29
1
1
Order By: Relevance
“…The airborne particle diameter increases with height as shown in Figs 10(a) and (b), but this property is inconsistent with some previous studies [4,7]. The wind tunnel experiment by Gromke et al [7] shows that the mean snow particle diameter is fairly constant with height in the saltation layer, whereas Nishimura et al [4] found from a field observation of blowing snow in Antarctica that the particle diameter distribution can be approximated by a gamma distribution, which moves to smaller diameters with height. These results show that the mean particle diameter decreases from the saltation layer to the suspension layer.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The airborne particle diameter increases with height as shown in Figs 10(a) and (b), but this property is inconsistent with some previous studies [4,7]. The wind tunnel experiment by Gromke et al [7] shows that the mean snow particle diameter is fairly constant with height in the saltation layer, whereas Nishimura et al [4] found from a field observation of blowing snow in Antarctica that the particle diameter distribution can be approximated by a gamma distribution, which moves to smaller diameters with height. These results show that the mean particle diameter decreases from the saltation layer to the suspension layer.…”
Section: Discussioncontrasting
confidence: 98%
“…According to experiments by Sugiura et al [3], the fluid threshold u f of compact snow particles is in the range of 0.19 ∼ 0.25 m s −1 ; therefore, we assume u f = 0.20 m s −1 . The particle size distribution at the granular bed is approximated by various functions depending on fields and experimental conditions, although the gamma distribution is used in our simulations on the basis of the experiment by Gromke et al [7] and the observation by Schmidt [20]. The diameter d of the entrained particle is selected from Γ(3, 100), where the mean, standard deviation, and peak are 300 µm, 100 √ 3 µm, and 200 µm, respectively.…”
Section: E Setup Of Numerical Simulationsmentioning
confidence: 99%
“…The acquired images show dark saltating crystals on a bright background (Figure c). The postprocessing of the images is conducted by applying image analysis for the detection of the particles and the estimation of their size and by employing an algorithm designed for Particle Tracking Velocimetry (PTV) [ LaVision , ; Gromke et al , ; Crivelli et al , ], as shown in Figure c. Preliminary experiments were conducted to calibrate the digital shadowgraphy [ Crivelli et al , ] using a calibrated Snow Particle Counter (SPC), which is considered the standard measurement technique for snow and sand mass fluxes [ Sato et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…The first wind tunnel experiments have investigated the contribution of the saltating particles to the aeolian snow transport by means of laser visualization and a photographic acquisition system [ Oura et al , ; Kobayashi , ] and later provided more quantitative information on the particle trajectories [ Araoka and Maeno , ; Sugiura et al , ]. Subsequently, photographic techniques were also employed to obtain mean profiles of velocity, particle concentration, mass flux, and particle dimension [ Naaim and Martinez , ; Naaim‐Bouvet and Naaim , ; Tominaga et al , ; Gromke et al , ], and later frequency analysis of the snow mass flux [ Paterna et al , ]. Mechanical traps and optical detectors were also largely employed to measure mean profiles and time series statistics [ Sugiura et al , ; Nishimura and Hunt , ; Nemoto and Nishimura , ; Kosugi et al , ; Clifton et al , ; Guala et al , ; Okaze et al , ], as well as to investigate the splash entrainment process [ Sugiura and Maeno , ; McElwaine et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Shadowgraphy images [ Gromke et al ., ] of the saltation layer were taken during the experiments to determine the particle mass flux Q . For this purpose, the saltation layer was illuminated with a light from one side of the wind tunnel, and shadow images of the particles were recorded with a high‐speed camera from the opposite side.…”
Section: Methodsmentioning
confidence: 99%